Erratum to: Algorithm of OMA for large-scale orthology inference - Roth, Alexander CJ; Gonnet, Gaston H; Dessimoz, Christophe (BMC bioinformatics, 2009)
Since the publication of our article (Roth, Gonnet, and Dessimoz: BMC Bioinformatics 2008 9: 518), we have noticed several errors, which we correct in the following.